Decision latitute, job demand, social support, burnout and perceptions of productivity among allied health educators in three allied health colleges with the Ministry of Health, Malaysia - Shahridah binti Kassim (Institute Education, International Islamic University Malaysia, 2010)
Work plays a central role in most of our daily lives. It provides many positive benefits in one's life as it brings out a sense of identity and self-esteem. However, stressful encounters during work can bring about negative outcomes emotionally, physically and physiologically. The main purpose of this study is to evaluate the structural model of job strain by using the Job-Demand-Control-Support (JDCS) model by Karasek ( 1979). The JDCS model predicts that job strain occurs when job demands are high and employee's job control is low. The vice-versa happens when an employee has high job demands and high job control. The samples involved in this study were 198 allied health educators from three Colleges of Allied Health Sciences in the Ministry of Health Malaysia. A cross-sectional survey has been carried out using the adopted version of instruments job content questionnaire (Karasek, 1985), Maslach burnout inventory (Maslach, 1982) and perceived productivity (Pierce 1989). The study was based on the assumption when psychological job demands are high and job control is low, burnout will develop. This eventually will affect educators' productivity. Two alternative models were tested for the best fit on a sample sizC'. This would then be extrapolated to the selected population. The structural model supported the competing model by which psychological job demand was the only predictor to productivity. The findings revealed that social support indirectly influenced productivity via burnout. The findings also revealed that decision latitude was positively correlated with psychological job demand, and social support was positively correlated with psychological job demand. The theoretical, methodological, practical implications of these results and directions for future research were provided.